2005
DOI: 10.4158/ep.11.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Liothyronine at a 1:5 Ratio for a Portion of Levothyroxine: Effect on Fatigue, Symptoms of Depression, and Working Memory Versus Treatment With Levothyroxine Alone

Abstract: Background-This study was planned at a time when important questions were being raised about the adequacy of using one hormone to treat hypothyroidism instead of two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 16 publications
0
76
0
Order By: Relevance
“…This raises the question of whether LT4-treated subjects with low T3 levels could benefit from low-dose LT3 therapy to assist with body weight regulation. However, all but one randomized controlled studies of combined LT4/ LT3 in hypothyroid subjects failed to find any differences in weight between combined LT4/LT3 and LT4 monotherapy (31)(32)(33)(34)(35)(36)(37)(38)(39). In addition, REE was not affected in the study by Celi et al (30).…”
Section: Lt4 Therapy Energy Expenditure and Body Compositionmentioning
confidence: 72%
“…This raises the question of whether LT4-treated subjects with low T3 levels could benefit from low-dose LT3 therapy to assist with body weight regulation. However, all but one randomized controlled studies of combined LT4/ LT3 in hypothyroid subjects failed to find any differences in weight between combined LT4/LT3 and LT4 monotherapy (31)(32)(33)(34)(35)(36)(37)(38)(39). In addition, REE was not affected in the study by Celi et al (30).…”
Section: Lt4 Therapy Energy Expenditure and Body Compositionmentioning
confidence: 72%
“…Most patients included in the present study had a high baseline psychological morbidity. But subset analyses of previous trials do not support this explanation (6,7,12,14), although there may be a sample size problem. Could it be something else?…”
Section: Randomized Controlled Trials: a Reappraisalmentioning
confidence: 85%
“…Although no relation was observed in the meta-analysis between the percentages of included athyreotic patients and the effect of combination therapy on symptoms, it is preferable to restrict inclusion to spontaneous autoimmune hypothyroidism as was done in the present RCT (2). Six studies in the meta-analysis had a crossover study design (5,6,7,10,12,13), and five studies had a parallel study design (8,9,11,14,15). Observations in crossover studies are not independent because the same patients receive both combination and monotherapy (1).…”
Section: Randomized Controlled Trials: a Reappraisalmentioning
confidence: 99%
“…Most studies have assessed changes in mood, cognition function and QoL during combination therapy with LT4/LT3 (11,12,21,(23)(24)(25)(26)28,(30)(31)(32)40,41). Two meta-analyses including 10 (14) and 11 (13) of these studies showed no improvement in bodily pain, well-being, mood, fatigue, QoL or cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis evaluating 11 randomized controlled trials with a total of 1,216 patients concluded that there is no evidence supporting the superiority of LT4/LT3 combination therapy regarding improvements in bodily pain, mood, fatigue, QoL, cognition, body weight or blood lipids (13). Not even patients with depression (11), high dissatisfaction with LT4 therapy (23), psychiatric symptoms (24), or fatigue (25) benefited from the combination therapy.…”
Section: Discussionmentioning
confidence: 99%